The key iron assimilation genes ClFTR1, ClNPS6 were crucial for virulence of Curvularia lunata via initiating its appressorium formation and virulence factors. (25th June 2020) - Lu, Yuanyuan; Sun, Jiaying; Gao, Yibo; Liu, Kexin; Yuan, Mingyue; Gao, Weida; Wang, Fen; Fu, Dandan; Chen, Nan; Xiao, Shuqin; Xue, Chunsheng
Summary: Iron is virtually an essential nutrient for all organisms, to understand how iron contributes to virulence of plant pathogenic fungi, we identified ClFTR1 and ClNPS6 in maize pathogen Curvularia lunata ( Cochliobolus lunatus ) in this study. Disruption of ClNPS6 significantly impaired siderophore biosynthesis. ClFTR1 and ClNPS6 did mediate oxidative stress but had no significant impact on vegetative growth, conidiation, cell wall integrity and sexual reproduction. Conidial germination delayed and appressoria formation reduced in Δ Clftr1 comparing with wild type (WT) CX‐3. Genes responsible for conidial germination, appressoria formation, non‐host selective toxin biosynthesis and cell wall degrading enzymes were also downregulated in the transcriptome of Δ Clftr1 and Δ Clnps6 compared with WT. The conidial development, toxin biosynthesis and polygalacturonase activity were impaired in the mutant strains with ClFTR1 and ClNPS6 deletion during their infection to maize. ClFTR1 and ClNPS6 were upregulated expression at 12–24 and 48–120 hpi in WT respectively. ClFTR1 positively regulated conidial germination, appressoria formation in the biotrophy‐specific phase. ClNPS6 positively regulates non‐host selective toxin biosynthesis and cell wall degrading enzyme activity in the necrotrophy‐specific phase. Our results indicated that ClFTR1 and ClNPS6 were key genes of pathogen known to conidia development and virulence factors.